Does symptom activity explain psychological differences in patients with irritable bowel syndrome and inflammatory bowel disease?: results from a multi-center cross-sectional study - Berens, Sabrina; Baumeister, David; Gauss, Annika; Eich, Wolfgang; Tesarz, Jonas (Journal of psychosomatic research, 2019)
Objective - Irritable bowel syndrome (IBS) and inflammatory bowel diseases (IBD) have similar symptoms and are affected by psychological factors via gut-brain-interactions. However, previous studies on IBS and IBD showed inconsistent results regarding psychological factors, potentially because they failed to consider the impact of symptom activity. The aim of this study was 1) to compare psychological distress and psychological risk factors among patients with IBS, IBD and healthy controls (HC), and 2) to assess the impact of symptom activity. - Methods - A controlled cross-sectional study was conducted. Patients with IBS and IBD were recruited in several primary, secondary, and tertiary medical care units between 02 and 12/2017 in Germany. Overall, 381 matched participants (127/group, 63% female) were included. For the second analyses, patients with IBD were distinguished in patients with active (n=93) and non-active (n=34) symptoms. Psychological distress (somatization, depression, anxiety, and illness anxiety) and risk factors (adverse childhood experiences, attachment style, and mentalizing capacity) were measured. - Results - Patients with IBS showed higher psychological distress and more psychological risk factors than patients with IBD and HC. However, patients with IBD and active symptoms showed similar psychological distress than patients with IBS, except for lower illness anxiety (p<.001, η2=0.069). - Conclusion - With the exception of higher illness anxiety in IBS patients, differences in psychological factors between patients with IBS and IBD were more strongly associated with symptom activity than with the underlying diagnosis. Therefore, this study challenges previous concepts of distinguishing functional and organic gastrointestinal diseases, but highlights the role of symptom activity and illness anxiety. - Trial registration - DRKS00011685.